Untitled (African Knowledges and the History Publication since the 1970s, 1983)
World news: Fifth brigade; Falkland's war; Rangoon bombing; assassination of Ninoy Aquino; 1983 Beirut barracks bombings; and assassination of Maurice Bishop.
Keywords: News